Fatherhood Reflected in Marc Foster’s Finding Neverland (2004) - Eka Nur Hidayati; Latifah Dwi Ariyani (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2021)
This study is aimed to analyze : (1) the fatherhood in Marc Foster’s Finding Neverland (2) the psychological statement of James Barrie who commit to be father in Marc Foster’s Finding Neverland. The research is in form of descriptive qualitative analysis in analyzing Marc Foster’s Finding Neverland (2004) movie as the object of the research. The data analyzed by using Psychology of Literature theory, Fatherhood theory, Anna Freud’s Defense Mechanism, and Alter Ego theory. The researcher uses two types of data sources, they are main data and supporting data. The method of collecting data includes watching and reading, identifying, classifying, simplying, and selecting. The methods of analyzing the data includes exposing, explaining, and interpreting. The result of the research, first, it shows that the main character reflected the fatherhood through the fulfillment of father’s roles he is doing in Marc Foster’s Finding Neverland such as being a companion, teacher, care provider, moral guide, role model, breadwinner, protector, and spouse. For the second, the psychological state of James James Barrie as he has psychological trauma, he uses repression and reversal as his defense mechanism to deal with his trauma, and he has also an alter ego or different personality.